THE NECESSITY OF IMPROVING ADMINISTRATIVE MEASURES AGAINST OFFENSES THREATENING PUBLIC SECURITY (European Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the current state of administrative measures against offenses that threaten public security, examining their effectiveness, systemic issues, and the necessity for improvement from a scientific perspective. It also reviews the experiences of countries such as Germany, Japan, and France, offering proposals for adapting these practices to the national legal mechanisms. In conclusion, the article presents legal, organizational, and technological solutions aimed at enhancing the relevant system.